130 Adaptation of IHI Joy-in-Work framework to reduce burnout among postgraduate trainees. (29th October 2021) - Hu, Zheng Jing; Fusch, Gerhard; el Helou, Salhab; Lehana, Thabane; Chan, Teresa; El Gouhary, Enas
Abstract: Primary Subject area: Physician Wellness Background: Physician burnout is a psychological phenomenon with serious and pervasive consequences on physicians' mental health, patient safety, and quality of care. Burnout is multifactorial, originating from systemic issues, organizational culture and individual coping skills. Burnout is more common in residency training. Residents experience burnout more intensely due to lack of autonomy, self-efficacy and exposure to mistreatment. Residents are also frontline workers and the future healthcare givers. Organization-led interventions mostly focus on building resilience and mindfulness without addressing systems-level issues. In our study, we attempted to shift the paradigm to address system-level concerns first. We aimed to adapt Joy-in-Work: a quality improvement framework developed by the Institute for Healthcare Improvement (IHI). This program allows residents to identify system problems that are meaningful to them and empower them to work as a team, taking back their autonomy and self-efficacy. Objectives: To demonstrate that Joy-in-Work can be adapted effectively into a residency training program to reduce burnout and improve psychological safety among residents. Design/Methods: The four steps of Joy-in-Work were implemented for residents in a level 3 neonatal intensive care unit. Residents engaged in "what matters" conversations through survey and group meetings, and identified impediments to Joy-in-Work. By applying QI methodology, residents identified priority interventions to eliminate impediments. Finally, the effectiveness of interventions was evaluated. Primary outcomes included prevalence of burnout and psychological safety; secondary outcomes assessed control over workload, and organizational culture. An IHI 12-item questionnaire was administered at baseline and after the interventions. To assess sustainability, a survey was also conducted one year after the implementation. We assessed adherence to interventions, nurse practitioners' satisfaction and residents' workload indicators. Results: Through the implementation of Joy-in-Work, residents identified autonomy and work life integration as priorities. Stakeholders developed two interventions: change call schedule according to residents' preferences and earlier afternoon handover time. Burnout was 77.8%, 50% and 75% for three survey periods respectively. Psychological safety increased consistently from 16.7% to 37.5% to 43.8%. Lack of control over workload dropped sharply from 72.2% to 12.5%, with a rebound to 56.3%. Most secondary outcomes demonstrated a similar pattern of positive change initially with reversion to baseline. Conclusion: We demonstrated that Joy-in-Work is successfully adaptable into a residency setting. Implementation through residents' engagement and empowerment can decrease burnout and improve psychological safety significantly. The process itself was likely the key driver for achieving positive outcomes rather than the actual interventions. Sustainability remains a key issue that requires systems support.